Characteristics of teacher turnover types in the public elementary school of Manila, 1959-1968 - Fermin, Adelinda Emma (Gajo) 1944- (s.n.], 1970)
The aim of the study is to determine the characteristics of the different school teachers from 1959-1968 according to certain demographic variables, professional variables, and "reasons for leaving." Findings of the study offer insights to existing problems which cause the turnover of valuable teachers.